Differential Diagnosis of Nonabsorbable Inflammatory and Malignant Subsolid Nodules with a Solid Component ≤5 mm - He XQ; Li X; Wu Y; Wu S; Luo TY; Lv FJ; Li Q (Dove Medical Press, 2022)
Xiao-Qun He,1,* Xian Li,2,* Yan Wu,3 Shun Wu,1 Tian-You Luo,1 Fa-Jin Lv,1 Qi Li1 1Department of Radiology, The First Affiliated Hospital of Chongqing Medical University, Chongqing, People's Republic of China; 2Department of Pathology, Chongqing Medical University, Chongqing, People's Republic of China; 3Nursing School, Chongqing Medical University, Chongqing, People's Republic of China*These authors contributed equally to this workCorrespondence: Qi Li, Department of Radiology, The First Affiliated Hospital of Chongqing Medical University, No. 1 Youyi Road, Yu Zhong District, Chongqing, 400016, People's Republic of China, Tel +86 15823408652, Fax +86 23 68811487, Email liqi89011721@163.comPurpose: To investigate the differential clinical and computed tomography (CT) characteristics of pulmonary nonabsorbable inflammatory and malignant subsolid nodules (SSNs) with a solid component ≤ 5 mm.Patients and Methods: We retrospectively analyzed 576 consecutive patients who underwent surgical resection and had SSNs with a solid component ≤ 5 mm on CT images. These patients were divided into inflammatory and malignant groups according to pathology. Their clinical and imaging data were analyzed and compared. Multiple logistic regression analysis was used to identify independent prognostic factors differentiating inflammatory from malignant SSNs. Furthermore, 146 consecutive patients were included as internal validation cohort to test the prediction efficiency of this model.Results: Significant differences in 11 clinical characteristics and CT features were found between both groups (P < 0.05). Presence of respiratory symptoms, distribution of middle/lower lobe, irregular shape, part-solid nodule (PSNs), CT value of ground-glass opacity (GGO) areas